2020
DOI: 10.1177/1533317519898996
|View full text |Cite
|
Sign up to set email alerts
|

Determining Middle-Aged and Older Adults’ Health Beliefs to Change Lifestyle and Health Behavior for Dementia Risk Reduction

Abstract: Background: Global population is getting older and the prevalence of dementia continuously increases. Understanding the related health beliefs is bound to enable lifestyle-based interventions that maximize public engagement in dementia risk reduction behaviors. The aim of this study was to determine health beliefs on dementia prevention behaviors and lifestyle changes and to determine the factors influencing these beliefs among middle-aged and older people in Turkey. Materials and Methods: This descriptive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 25 publications
8
25
0
Order By: Relevance
“…Further, highly educated participants perceived more benefits and less barriers to perform healthy behaviours and had more confidence in their ability to perform the desired behaviour. These findings are in line with previous findings [ 15 , 20 ]. Only two previous studies reported MCLHB-DRR subscale scores reflecting the health beliefs and attitudes towards dementia (risk reduction) among the Australian (50 years and older) and Turkish (40 years and older) population [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Further, highly educated participants perceived more benefits and less barriers to perform healthy behaviours and had more confidence in their ability to perform the desired behaviour. These findings are in line with previous findings [ 15 , 20 ]. Only two previous studies reported MCLHB-DRR subscale scores reflecting the health beliefs and attitudes towards dementia (risk reduction) among the Australian (50 years and older) and Turkish (40 years and older) population [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in line with previous findings [ 15 , 20 ]. Only two previous studies reported MCLHB-DRR subscale scores reflecting the health beliefs and attitudes towards dementia (risk reduction) among the Australian (50 years and older) and Turkish (40 years and older) population [ 14 , 15 ]. In comparison to our study, these studies showed slightly higher scores on a number of subscales of the MCLHB-DRR scale.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These perceptions about dementia can also be negatively affected by inaccurate knowledge about dementia. If someone’s level of awareness for the causes and symptoms of dementia is low, they are less likely to participate in preventive activities for dementia, which may lead to delayed diagnosis and treatment [ 10 , 11 ]. Therefore, knowledge and perceptions about dementia is very important for the proper management of the disease [ 12 ].…”
Section: Introductionmentioning
confidence: 99%